Mekong River Delta crop decision tree for rice - Le Tam Thi; Huong Nguyen Mai; Kim, Kwang Hyung; Swaans, Cornelis P.M. (2022)
Crop decision tree is a systematic tool for the development of climate risk responses based on sub-seasonal and seasonal forecasts. This generates tailored agricultural advisories to farmers to cope with occurring climate risks taking location and crop growth stage into account. This document is the drafted decision trees for Mekong Delta region for rice crop.